The Challenge of Rapid Development Amidst International Debt in Sub-Saharan Africa: Nigeria’s Legal Framework and Pathways to Sustainable Debt Management - Antai, Godswill Owoche; Adebowale, Hassan; Nwaechefu, Hilary; Obisesan, Olawunmi Opeyemi; Aidonojie, Paul Atagamen; Ikpotokin, Omobolanle Omolola (NIU Journal of Social Sciences; Vol 10 No 4 (2024): NIU Journal of Social Sciences, Vol. 10 No. 4 December 2024DO - 10.58709/niujss.v10i4.2025, 2024)
Africa is no longer the frontier for new expansion like before the colonial era when Developed nations carved the African continent like a nice piece of chocolate cake. Anyone who still thinks this way does not fully grasp the implications of debt dealing and the mouse trap of international borrowing and underdevelopment. Africa is still the major frontier for European and oriental expansion but this time rather than sending troops on the ground the battle is economic. The struggle is also philanthropically disguised in initiatives by international financial and non-financial organizations that are loyal to the developed nations. This work is not a debate as to the veracity of the claims made here rather this work is squarely focused on the challenge of Nigerian external debt in recent times. The voyage is designed to examine the legal framework over external debt management in Nigeria while seeking adaptable solutions that would end the culture of international borrowing and make sure there are real economic gains made viz a viz the culture of running abroad for loans for capital projects. Borrowing for Nigeria pre-dated the existence of the Nigerian democracy because at the time when the earliest international loans were taken, the Brits were still in control around 1958, and the sum of Twenty-Eight Million ($28 Million) was obtained to ensure the construction of the Nigerian railway system. The research shows that indeed there are a handful of legislations within the country that regulate and marshal out both the powers and parameters of securing and servicing external debt, however, there is a disconnect somewhere that leads to many hindrances on the growth of the nation's GDP. It is the objective here to through the examination of existing laws discover the missing link and make recommendations for better arrangements. Invariably there will be lessons from looking at the legal framework vis-a-vis the sub-Saharan African layout. Indeed, developing economies must now focus within and desire more alternatives for raising capital than simply relying on foreign debt or international debt or external debt to raise capital for infrastructural projects within the nation or for even running the government. Keywords: International debt, Debt servicing, Financing, Debt Refinancing, Nigerian, World Bank